COMPARATIVE OF STOCK PRICE BEFORE AND AFTER INDONESIAN PRESIDENTIAL ELECTION IN 2014 OF LQ-45 STOCK LISTED ON IDX - Lie, Dave Danie; Pangemanan, Sifrid S.; Tumiwa, Johan (Universitas Sam Ratulangi, 2015)
Recently, investors have knowledge on investment for their future benefits. Then, as time goes by, they found out that information about some events may have a significant influence on the performance of the stock price and it makes them worry if this kind of event could affect the price of their shares, especially the price of LQ-45 stocks. One of the events that may affect the stock price is presidential election because it is macroeconomics factor that affect all aspects in the country including investment. This research conducted to identify the significant change of the stock price and to know if this event has an effect on price of LQ-45 Stock. This research uses Time Series Analysis, Paired Sample t-Test and purposive sampling method where the sample of this research is all LQ-45 stocks in IDX. The correlation result finds that there is a relation between stock price and presidential election. There is also a significant change on stock price after the presidential election. Therefore, it concluded that event such as presidential election is one of the factors that affect the performance of the stock price and investors recommended to be more cautious of information while doing stock transaction, and makes better investment. Â Keywords: stock price, presidential election, event study